Thermoformed Aligner Therapy for Presurgical Orthodontic Preparation in a Cleft Lip and Palate Patient With Multiple Sclerosis - Cynthia Dabed; Ignacio Fuentes; Gabriela La Valle (Journal of Craniofacial Surgery, 2026)
We present a 15-year-old female with a complete right unilateral cleft lip and palate (UCL/P), no prior alveolar bone graft, and multiple sclerosis (MS) requiring periodic MRI monitoring, in whom metallic fixed appliances were contraindicated. A sequence of 18 thermoformed aligners per arch achieved dentoalveolar expansion, alignment, leveling, torque correction, and preparation of the alveolar cleft site over ~10 months, including strategic extraction of a palatal supernumerary tooth 3 months before grafting. MRI follow-up proceeded without interference. This case demonstrates that thermoformed aligners constitute a viable and effective presurgical orthodontic alternative within multidisciplinary UCL/P management when metallic appliances are systemically contraindicated.